Application of Restorative Justice in the Crime of Theft - Dina Safitri (NEGREI: Academic Journal of Law and Governance, 2022)
The concept of restorative justice is also implemented in the Prosecutor's Office of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice . The concept of restorative justice is also implemented in the Prosecutor's Office of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice . The Tulang Bawang District Prosecutor's Office, Lampung, Indonesia has implemented restorative justice for the crime of petty theft committed by the defendant with the initials BC based on the Decree on Termination of Prosecution of the Head of the Tulang Bawang District Prosecutor's Office Number: PRINT- 01/L.8.4.18/Eoh.2/ 01/2022 dated 27 January 2022 (RJ-14). The purpose of this study was to find out the legal arrangements regarding restorative justice in the settlement of petty theft cases, to find out the application of restorative justice in the settlement of petty theft cases at the Tulang Bawang District Prosecutor's Office, and to find out the obstacles for the Tulang Bawang district attorney to implement restorative justice. in the crime of petty theft committed by Defendant BC. The research method used is a normative method using a juridical approach by managing primary legal materials, secondary legal materials and tertiary legal materials. The results of the study show that the legal arrangement regarding restorative justice in the settlement of cases of minor theft crimes is Perma Number 2 of 2012 concerning Adjustment of Limits for Minor Crimes which prioritizes restorative justice Police Circular Letter Number SE/8/VII/2018 concerning Application of Restorative Justice ). The application of restorative justice in the settlement of cases of minor theft crimes at the Tulang Bawang District Attorney is guided by the Republic of Indonesia Attorney General's Regulation No. 15 of 2020 because the defendant is the first time he has committed a crime. Obstacles for the Tulang Bawang District Prosecutor's Office in implementing restorative justice in the settlement of cases of minor theft crimes are that there are negative views and a lack of knowledge regarding community restorative justice, the large number of cases of theft that cannot be applied to restorative justice and the duration of time for making peace is too short.